Governing Alternative Resources for Social Policy: A Welfare Political Challenges on Mixed-Welfare Arrangements - Tauchid Komara Yuda (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2017)
The issue of social policy development in Indonesia has received considerable critical attention due often not consider non-state actor in the welfare provision. Data from several studies show that welfare system of contemporary Indonesia commonly fits with mix regime model, where the state, kinship relation, and markets play important role in provide social welfare for the society simultaneously. Accordingly, the greater efforts are needed to ensure that policy maker could regulate the ability to stimulate the compatible actor with likely welfare outcomes expected. By taking the empirical case of the Program Bedah Rumah Swadaya in Kulon Progo Regency Yogyakarta, this paper would examine the welfare politics that put community and market institutions as alternative resources to provides the decent houses for disadvantage groups. Correspondingly, this account composed into the three of main parts. The first part begins by laying out a brief overview of the foundation of Kulon Progo welfare system. The second part would identify how the political citizenship dimension is carried out through this programs. While the last part captures the resource arrangements in housing provision.